THE EFFECT OF CLICKKB APPLICATION MEDIA ON THE SELF EFFICACY OF COUPLES OF REPRODUCTIVE AGE IN CONTRACEPTIVE USE - Izza Qurotaaini; Sri Rahayu; Hening Ryan Aryani (SEAJOM: The Southeast Asia Journal of Midwifery, 2023)
Self-Efficacy is an important factor in selection and use of contraception. Lack of confidence in using contraception will have negative impact on individual psychological problems. This is due to lack social support from health workers regarding self-efficacy contraceptive. This study aims to determine the effect of KlikKB application media on the self-efficacy of couples childbearing age in use of contraception. Method Pre-experimental with one group pretest-posttest. The population in this study was 43 couples of childbearing age who used injection contraception for 1 month. The sample uses a total sampling technique. Data collection was carried out in April – July 2022. The research instrument was in form of questionnaire. Data analysis using Wilcoxon test. The results showed that there was an increase in self-efficacy in using contraception by giving the KlikKB application before (69.8%), after (76.7%). The test results value of 0.000 <0.05, which means that there is an influence of the KlikKB application media on the self-efficacy of couples of childbearing age in use of contraception. The conclusion of this study is that there is an influence of the KlikKB application media because it can increase self-efficacy in the use of contraception.